Sedentary behaviour research in adults: A scoping review of systematic reviews and meta-analyses. Issue 19 (2nd October 2021) - Memon, Aamir Raoof; Stanton, Robert; To, Quyen; Schoeppe, Stephanie; Urooj, Anum; Alley, Stephanie; Hayman, Melanie; Vandelanotte, Corneel
ABSTRACT: Sedentary behaviour research is rapidly growing. Scoping reviews are important to inform policy and practice.The aim of this scoping a review was to map the available evidence from systematic reviews and meta-analyses of sedentary behaviour research on adults (≥18 years), within the phases of the behavioural epidemiology framework, and to identify bibliometric parameters of studies included in this review. Nine bibliographic databases were searched. Studies were screened and relevant information (e.g., general information, inclusion criteria, findings and reporting quality) was extracted independently by two authors. In total, 108 systematic reviews and/or meta-analyses of sedentary behaviour research in adults (≥18 years) were included. Most papers (91.7%) were published between 2010 and 2020. Studies on the relationship of sedentary behaviour with health (53.7%) and interventions to reduce sedentary behaviour (25.9%) were most common. Forty-five (41.7%) studies reported quality assessment with categorization, and 887 out of 1268 (70%) included primary studies were categorized having moderate-to-high quality. Sedentary behaviour research on adults (≥18 years) has grown exponentially in the last decade and demonstrates strength in several stages of the behavioural epidemiology framework. However, more research should focus on the measurement, prevalence/epidemiology and determinants of sedentary behaviour, to better inform policy development.